Identification of novel potential inhibitors of varicella-zoster virus thymidine kinase from ethnopharmacologic relevant plants through an in-silico approach - Kwofie, S.K.; Annan, D.G.; Adinortey, C.A.; Boison, D.; Kwarko, G.B.; Abban, R.A.; Adinortey, M.B. (Taylor & Francis Group, 2021)
Although Varicella or chickenpox infection which is caused by the varicella-zoster virus (VZV) has sig nificantly been managed through vaccination, it remains an infection that poses threats to the nearest future due to therapeutic drawbacks. The focus of this research was geared towards in silico screening for the identification of novel compounds in plants of ethnopharmacological relevance in the treat ment of chicken pox in West Africa. The work evaluated 65 compounds reported to be present in Achillea millefolium, Psidium guajava and Vitex doniana sweet to identify potential inhibitors of thymi dine kinase, the primary drug target of varicella zoster virus. Out of the 65 compounds docked, 42 of these compounds were observed to possess binding energies lower than 7.0 kcal/mol, however only 20 were observed to form hydrogen bond interactions with the protein. These interactions were eluci dated using LigPlotþ and MM-PBSA analysis with residue Ala134 predicted as critical for binding. Pharmacological profiling predicted three potential lead compounds comprising myricetin, apigenin- 4’ -glucoside and Abyssinone V to possess good pharmacodynamics properties and negligibly toxic. The molecules were predicted as antivirals including anti-herpes and involved in mechanisms comprising inhibition of polymerase, ATPase and membrane integrity, which were corroborated previously in other viruses. These drug-like compounds are plausible biotherapeutic moieties for further biochemical and cell-based assaying to discover their potential for use against chickenpox.
Research Article
Keywords: Chickenpox; varicella zoster virus; thymidine kinase; molecular docking; molecular dynamics simulations